1985
DOI: 10.1111/j.1570-7458.1985.tb03531.x
|View full text |Cite
|
Sign up to set email alerts
|

Host plant selection by the pollen beetle Meligethes aeneus

Abstract: A simple bioassay is described for the response of Meligethes aeneus F. (Coleoptera: Nitidulidae) to different plants and plant parts. Assays with non‐hibernated beetles showed that (1) cruciferous buds and stamens were greatly preferred to petals and leaves; (2) stamens were most preferred when the quantity of mature pollen was at maximum; (3) anthers were preferred to filaments; (4) stamens from five different spring cultivars of Brassica napus were preferred at significantly different degrees; (5) stamens f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…However, the difference could also be qualitative, due to chemical differences between the volatiles emitted by anthers and the rest of the flower, as observed in other species (Dobson et al, 1990). Charpentier (1985) tested the relative attractiveness of different oilseed rape plant parts to pollen beetles and found that the beetles could discriminate between them, preferring anthers over leaves, filaments, petals, and buds. Although visual and tactile cues were not removed from his bioassay, Charpentier proposed that the odour of anthers was particularly important in this attraction, and his work supports the possibility that chemical differences between the anthers and other floral parts of oilseed rape exist and that these are detectable by the pollen beetle.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference could also be qualitative, due to chemical differences between the volatiles emitted by anthers and the rest of the flower, as observed in other species (Dobson et al, 1990). Charpentier (1985) tested the relative attractiveness of different oilseed rape plant parts to pollen beetles and found that the beetles could discriminate between them, preferring anthers over leaves, filaments, petals, and buds. Although visual and tactile cues were not removed from his bioassay, Charpentier proposed that the odour of anthers was particularly important in this attraction, and his work supports the possibility that chemical differences between the anthers and other floral parts of oilseed rape exist and that these are detectable by the pollen beetle.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies have compared life history traits of adults and larvae of this pest among different brassicaceous species Charpentier 1985;Borg and Ekbom 1996;Ekbom and Borg 1996;Hopkins andEkbom 1996, 1999;Ekbom 1998;Hopkins et al 1998;Billqvist and Ekbom 2001;Bartlet et al 2004;Cook et al 2007;Veromann et al 2012Veromann et al , 2014Kovács et al 2013;Kaasik et al 2014a, b). These results are summarized in Fig.…”
Section: Introgression Of Resistance From Other Brassicaceous Speciesmentioning
confidence: 97%
“…At this stage, other chemical stimuli (surface and/or inner tissue semiochemicals) gained from close inspection of the plant become more important. Indeed, Charpentier (1985) found differences between host-plant feeding preferences of pollen beetles and concluded that chemical stimuli were the most important. Hervé et al (2014) studied these stimuli by comparing six OSR genotypes for pollen beetle feeding preference, and identified possible phagostimulant/deterrent compounds in the bud perianth (the tissue that has to be pierced to access the food source) and in anthers (the tissue containing the food source).…”
Section: Food Host-plant Acceptance (Short Range/contact Cues)mentioning
confidence: 99%
“…In laboratory tests, pollen beetles have been found to be attracted to volatiles from OSR in the bud stage (Evans and AllenWilliams 1994;Cook et al 2007c;Jönsson and Anderson 2007), at the flowering stage (Evans and Allen-Williams 1994;Cook et al 2002Cook et al , 2006b, to floral volatiles from the OSR flower or part of the flower (Charpentier 1985;Byers 1992;Cook et al 2002), as well as to pollen odour (Cook et al 2002). The chemical basis for this attraction has been tested in the laboratory using electrophysiological studies and the most active compounds include 2-phenylethyl-, 3-butenyl-and 4-pentenyl-isothiocyanate, phenlyacetaldehyde and indole (Cook et al 2007c).…”
Section: Finding Host-plantsmentioning
confidence: 99%